Rhizospheric Bacillus amyloliquefaciens Protects Capsicum annuum cv. Geumsugangsan From Multiple Abiotic Stresses via Multifarious Plant Growth-Promoting Attributes - Kazerooni, Elham Ahmed; Maharachchikumbura, Sajeewa S. N.; Adhikari, Arjun; Al-Sadi, Abdullah Mohammed; Kang, Sang-Mo; Kim, Lee-Rang; Lee, In-Jung (Frontiers in Plant Science, 2021)
Plant growth-promoting rhizobacteria (PGPR) are beneficial microorganisms that can be utilized to improve plant responses against biotic and abiotic stresses. In this study, we investigated whether PGPR (Bacillus amyloliquefaciens) isolated from the endorhizosphere of Sasamorpha borealis has the potential to sustain pepper growth under drought, salinity and heavy metal stresses. The bacterial strain was determined based on 16S rDNA and gyrB gene sequencing and characterized based on the following biochemical traits: nitrogen fixation; 1-aminocyclopropane-1-carboxylate deaminase activity; indole acetic acid production; inorganic phosphate, potassium, zinc, and silicon solubilization; and siderophore production. Various abiotic stresses were applied to 28-day-old pepper seedlings, and the influence of the PGPR strain on pepper seedling growth under these stress conditions was evaluated. The application of PGPR improved survival of the inoculated pepper plants under stress conditions, which was reflected by higher seedling growth rate and improved physiochemical traits. The PGPR-treated plants maintained high chlorophyll, salicylic acid, sugar, amino acid, and proline contents and showed low lipid metabolism, abscisic acid, protein, hydrogen peroxide contents and antioxidant activities under stress conditions. Gene expression studies confirmed our physiological and biochemical findings. PGPR inoculation led to enhanced expression of XTH genes and reduced expression of WRKY2, BI-1, PTI1 and BiP genes. We conclude that the PGPR strain described in this study has great potential for use in the phytoremediation of heavy metals and for enhancing pepper plant productivity under stress conditions, particularly those involving salinity and drought.